PENERAPAN SISTEM AKUNTANSI PEMBIAYAAN MURABAHAH PADA PT BANK ACEH SYARIAH CABANG PEMBANTU ISKANDAR MUDA - Syahrul Muhammad Nur (JURNAL KREASI RAKYAT, 2023)
Sharia banking is an institution that provides financial services to the community where all activities are carried out based on Islamic ethics and principles so that they are free from the element of usury (interest), free from non-productive speculative activities such as gambling (maysir), free from illegal matters (bathil ), free from questionable activities (gharar), and only finance halal businesses. In its development, sharia banking is increasingly in demand by the wider community, one of its products is Murabahah financing, namely goods sales transactions that state the acquisition price and profits agreed upon in advance between the seller and the buyer. Implementation of murabahah contract financing at PT Bank Aceh Syariah Iskandar Muda Sub-Branch, the use of an accounting information system is very much needed by accounting users, both from internal parties and the Bank. System development must be carried out periodically to improve information quality, improve internal control, and minimize related costs. The approach used in research is empirical, namely, an effort to approach the problem being studied by reality. The data sources used include primary data and secondary data. Data collection techniques in this research were conducted using interview methods, literature study, and documentation. From the results of research conducted by researchers, it can be concluded that the implementation of the Murabahah Financing Accounting System and in providing Murabahah financing to customers at PT Bank Aceh Syariah Iskandar Muda Sub-Branch is in line with sharia principles and by the provisions of the Statement of Financial Accounting Standards (PSAK) No. 102.